Wide-Angle Polarization-Independent Broadband Absorbers Based on Concentric Multisplit Ring Arrays - Bin Tang; Yiqi Zhu; Xin Zhou; Li Huang; Xianzhong Lang (IEEE Photonics Journal)
We theoretically propose a wide-angle, polarization-independent, and broadband nearly perfect absorber, which consists of an array of concentric multisplit circular rings on top of dielectric spacer and a metallic mirror. The numerical simulation results show that the average absorption reaches 97.2% over the wavelength range from 585 to 800 nm whatever the polarization angle is. Meanwhile, the absorber keeps high absorption efficiency when the incidence angle is below 45°. The physical mechanism is analyzed by calculating the absorbed power spectra and electromagnetic field distribution. The broadband and the high absorption mainly result from the strong electromagnetic resonance and overlapping of resonant frequencies. Our proposed plasmonic absorbers have potential applications in spectral imaging, photodetector, solar energy, and so on.